The Importance of Klebsiella pneumoniae as a Pathogen and the Increasing Prevalence of Antibiotic-Resistant Strains and Molecular Characteristics - Waleed Mohammed; Fatimah Abdulazeez Awad; Thana I. Mustafa (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Klebsiella pneumoniae is a significant pathogen causing various infections, and antibiotic-resistant strains of K.pneumoniae are becoming more prevalent. Molecular studies reveal the genetic mechanisms underlying antibiotic resistance, such as resistance genes on plasmids that can easily spread between bacteria. Knowledge of the molecular characteristics of antibiotic-resistant strains is crucial to develop effective strategies against their spread. The bacteria can easy colonizes the human gut and can also cause a range of infections, including pneumonia, urinary tract infections, and bloodstream infections.